Komersialisasi Vaksin Covid-19 dan Tes PCR di Indonesia pada Masa Pandemi sebagai Implikasi dari Kerancuan Wacana Demokrasi : Komersialisasi Vaksin Covid-19 dan Tes PCR di Indonesia pada Masa Pandemi sebagai Implikasi dari Kerancuan Wacana Demokrasi - Rieka Yulita Widaswara; John Abraham Ziswan Suryosumunar; Fuad Noorzeha (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
This paper was conducted by authors based on research about the reality of the policy for handling the Covid-19 pandemic in Indonesia, which has many pros and cons in the Indonesian people. Especially related to the existence of paid vaccinations and the issue of the PCR test business which is indicated to involve the political elite. Based on this background, the authors conducted a literature study to uncover the link between the commercialization of medical devices during the pandemic with the confusion of democratic discourses understood through a teleological perspective. The philosophical hermeneutic method is used by authors to be able to analyze in depth the implications of the confusion of democratic discourse on the existence of paid vaccines and the PCR test business. The discussion in this study resulted in conclusions, namely: (1) teleological theory is a theory that refers to purposes-oriented understanding. Its main basis is the doctrine of concequencialsm and welfarism which leads to general happiness. (2) Democracy is a discourse that describes a system of governance that idealizes social justice and people's sovereignty, but the implementation of democracy seen from a teleological perspective has always never reached its ideal purposes because it is based on public representation that does not really represent it as a whole. (3) The business issue of PCR testing and paid vaccines explains the implications of the confusion of democratic discourse, because democracy is considered as a proposition that explains the final truth and tends to be potentially used as a tool of political hegemony that reduces the interests of the people